1976
DOI: 10.1093/bja/48.5.447
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Gaseous Homeostasis and the Magill Circuit Using Low Fresh Gas Flows

Abstract: Gas concentrations and ventilation levels have been measured within a conventional Magill circuit when conscious volunteers breathed a non-narcotic gas mixture at varying fresh gas flows. When evidence of rebreathing of alveolar gas was detected, the fresh gas flow was kept constant until a steady state developed. All subjects showed evidence of rebreathing when the fresh gas flow approached the predicted alveolar ventilation levels. A variety of subject-circuit interactions was seen and shown to be precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These may be described as the "Enclosed Mapleson A" (EMA) and the "Enclosed Preferential Flow" (EPF) systems. The conventional Mapleson A system and its modifications have been shown to require a minimum fresh gas flow almost equal to the alveolar minute volume of ventilation during spontaneous ventilation [9][10][11][12][13]. During controlled ventilation the flow dynamics change completely as gas is eliminated from the system during the inspiratory phase instead of during the expiratory phase as in spontaneous ventilation.…”
mentioning
confidence: 99%
“…These may be described as the "Enclosed Mapleson A" (EMA) and the "Enclosed Preferential Flow" (EPF) systems. The conventional Mapleson A system and its modifications have been shown to require a minimum fresh gas flow almost equal to the alveolar minute volume of ventilation during spontaneous ventilation [9][10][11][12][13]. During controlled ventilation the flow dynamics change completely as gas is eliminated from the system during the inspiratory phase instead of during the expiratory phase as in spontaneous ventilation.…”
mentioning
confidence: 99%
“…The fresh gas flow rate required to prevent rebreathing in the Mapleson A (Magill) anaesthetic breathing system has been studied extensively in anaesthetized patients [1] and conscious volunteers [2,3]. These authors agreed with the conclusions of the theoretical analysis performed by Mapleson [4] and found that rebreathing did not occur until fresh gas flow was reduced to approximately alveolar minute volume.…”
mentioning
confidence: 56%
“…The virtue of the Magill (Mapleson A) anaesthetic system with its low resistance to gas flow and its economy of fresh gases in spontaneously breathing patients is well established (Mapleson, 1954;Kain and Nunn, 1968;Norman, Adams and Sykes, 1968;Sykes, 1968;Conway et al, 1976). The Mapleson D (Bain Modification) system with the expiratory control valve situated remote from the patient and its economy of fresh gas flow with controlled ventilation is useful in many situations (Bain and Spoerel, 1972;Conway, Seeley and Barnes, 1977).…”
mentioning
confidence: 99%